Literacy as a Strategy for Improving the Quality of Education - Dewi, Anita Candra; Ichsan, Muhammad Farichul; Munandar, Isra Agustina Al; Laele, Muhammad Afdhal; Hajar, Nurwahyuni; Mira (International Journal of Sustainability in Research, 2023)
This research aims to provide an understanding of the important role literacy plays in the world of education for the progress of students for the nation and state. Literacy exists and is provided from an early age as a means to increase students' knowledge so that education becomes much better. The type of research used is qualitative research with a descriptive approach. The data collection technique used by the author is literature study. Literacy provides many benefits, improving the quality of human resources for educational progress.